Template-Assisted Assembly: Scanning Tunneling Microscopy Study of Solvent-Dependent Adlattices of Alkyl-Derivatized Tetrathiafulvalene - Lee, Shern-Long; Chu, Yi-Chen; Wu, Hung-Jen; Chen, Chun-hsien (Langmuir, 2012)
The self-assembly of an adsorbate as a function of the strength of solvent–substrate adsorption is an important yet relatively unexplored subject. In this study, how the strength of solvent–substrate adsorption and solvent–solvent attraction affects the assembly of tetrakis(octadecylthio)tetrathiafulvalene (1) is scrutinized by scanning tunneling microscopy (STM). For solvents with strong intermolecular interactions and adsorption onto graphite, such as long n-alkanes (C n H2n+2, n ≥ 13), STM reveals that the solvent molecules form lamellae which become a template to direct the assembly of 1 into one-dimensional arrays. The lengths of one of the unit cell vectors for the assemblies are increased and well correlated with the solvent sizes. In situ STM monitoring of 1 introduced onto graphite with preadsorbed n-tetradecane adlattices shows that the developed assemblies of 1 have striped features aligned parallel to the underlying template. In contrast, for solvents with weak adsorption, such as short n-alkanes (C n H2n+2, n ≤ 12), toluene, and 1,2,4-trichlorobenzene, the adlattice structures of 1 are solvent-independent.